Comparison of pharmacokinetics and safety of albuvirtide in healthy subjects after intravenous drip and bolus injection - Qin, Huiling; Yao, Cheng; Zhang, Wei; Hu, Wei; Liu, Yuantao; Yu, Shuchang; Xie, Dong; Hu, Min; Ye, Jun (Naunyn-Schmiedeberg's archives of pharmacology, 2024)
Albuvirtide (ABT) is the first long-acting HIV fusion inhibitor developed in China, blocking the invasion of HIV-1 virus into target cells. This study aimed to compare the pharmacokinetics (PK), tolerability, and safety of ABT following a single intravenous (IV) bolus injection or intravenous drip in healthy Chinese subjects. A single-center, randomized, open-label, single-period, parallel phase I clinical trial was conducted. Thirty subjects were randomly divided into three groups in a ratio of 1:1:1. After an overnight fast, all subjects received a single dose of 320 mg ABT either by intravenous drip for 45 min (group A) or bolus injection for 0.5 min (group B), or bolus injection for 3 min (group C). ABT plasma concentrations were analyzed using a validated enzyme-linked immunosorbent assay (ELISA). Non-compartmental analysis was used to evaluate PK parameters. The median time to reach maximum concentration was 0.75 h in group A and 0.16 h in both groups B and C. Elimination half-life, mean residence time, apparent clearance, and apparent volume of distribution were similar among the three groups. The 90% confidence intervals (CI) of geometric mean ratios of PK parameters for groups B and C relative to group C were within 85–120%. All adverse events (AEs) reported in this study were mild, according to the CTCAE guidelines and the study investigator’s judgement. ABT bolus injections for 0.5 min and 3 min are expected to be well tolerated and to exhibit similar PK characteristics as IV drip for 45 min, offering potential clinical benefits.